Aktivna mehka snov - Zajc, Klemen (Matrika, 2014)
Soft active matter is recently a very popular topic among scientist. It consist of active objects, which alone move randomly, but when in group they show special arrangements. They appear on length scales from sub-cellular to oceanic. In this article is described division into polar or nematic and in wet or dry systems, followed by simplified description of both polar and nematic dry systems. In the final section are presented some latest experiments which reveal characteristics of the active matter and at the same time encourage the development of theoretical models.
Keywords: active liquid crystals; active matter; aktivne snovi; aktivni tekoči kristali; fizika mehke snovi; soft matter physics